Art embroidery as a way of formation of aesthetic culture of the future teachers of the fine arts - Stefanyuk, T.P. (Pedagogy of Higher and Secondary Education, 2007)
In article ways of formation of aesthetic culture of the future teachers of the fine arts are considered.